Implementation of screening, brief intervention, and referral to treatment (SBIRT) by nurses on acute care units: A qualitative descriptive study. Issue 4 (2nd October 2021) - Thoele, Kelli; Draucker, Claire Burke; Newhouse, Robin
Abstract: Background: Screening, Brief Intervention, and Referral to Treatment (SBIRT) is an evidence-based intervention for patients with substance use disorders, but this intervention is under-utilized. Little is known about the implementation of SBIRT in acute care facilities. The purpose of this study is to describe implementation of SBIRT by nurses in acute care hospitals. Methods : A qualitative descriptive design was used for this study. Registered nurses who agreed to participate in the study completed a 1:1 interview using a semi-structured interview guide. Interviews were audio recorded and transcribed and then data were analyzed using qualitative content analysis. Results : When implementing SBIRT in an acute care setting, participants identified several factors that affect implementation. Some nurses felt that it is "one more thing to do" but other nurses feel that it was a "good, simple" screening tool that does not take long to do and can "plant the seeds of change" for patients. Additionally, participants mentioned barriers and facilitators related to the patients' responses to SBIRT and organizational factors. Conclusions : This study identified several barriers and facilitators to SBIRT implementation related to the nurses, patients, and organization. By understanding the factors that influence implementation, healthcare providers can develop strategies to support effective implementation of SBIRT.